2014
DOI: 10.7710/2162-3309.1121
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Communication at Canadian Research Libraries: Conversations with Librarians

Abstract: INTRODUCTION The landscape of librarianship in relation to the practice of scholarly communication is evolving. The objectives of this study were to investigate: the scope of scholarly communication activities within Canadian research libraries; the organizational structures in place to support them; and the roles of librarians who participate in them. Key challenges to its advancement and how librarians envision its future were also investigated. METHODS Twenty-nine academic librarians from Canadian Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In smaller institutions, scholarly communication initiatives may be "more likely to be led by a single person, and much less likely to be led by a library unit" (Thomas, 2013, p. 168). Although Burpee and Fernandez (2014) concluded that organizational structure and leadership are essential drivers of scholarly communication initiatives (p. 16), a survey of ARL member libraries found that no single leadership model was predominant, as a mixture of single librarians and committees was responsible for steering initiatives (Radom, Feltner-Reichert, & Stringer-Stanback, 2012, p. 11).…”
Section: Scholarly Communication Job Responsibilities In Academic Libmentioning
confidence: 99%
See 1 more Smart Citation
“…In smaller institutions, scholarly communication initiatives may be "more likely to be led by a single person, and much less likely to be led by a library unit" (Thomas, 2013, p. 168). Although Burpee and Fernandez (2014) concluded that organizational structure and leadership are essential drivers of scholarly communication initiatives (p. 16), a survey of ARL member libraries found that no single leadership model was predominant, as a mixture of single librarians and committees was responsible for steering initiatives (Radom, Feltner-Reichert, & Stringer-Stanback, 2012, p. 11).…”
Section: Scholarly Communication Job Responsibilities In Academic Libmentioning
confidence: 99%
“…Fortunately, UNESCO has recently released online their Open Access Curricula for Researchers and Library Schools. Consisting of two components-a Institutional repositories (IRs) have become another cornerstone of library scholarly communication initiatives (Burpee & Fernandez, 2014;Carpenter, 2011;Radom et al, 2012;Staley, et al, 2010;Thomas, 2013). IRs provide "a natural entree for conversations about scholarly communication issues" (ARL, 2010, p. 289), and given tight budgets, many academic libraries (regardless of institution size) are attracted to open-source IR systems to cost-effectively engage in scholarly communication initiatives (Hashim & Jan, 2011).…”
Section: Scholarly Communication Education For Librariansmentioning
confidence: 99%
“…More holistic commentary on SC librarianship includes that from Carpenter, Graybill, Offord, and Piorun (2011), who projected that "Librarians can play a primary role in managing information for projects of all sizes, including bibliographic management, data creation and preservation, usage-rights, and assisting with the distribution of finished works and raw data by promoting open access" (p. 669). These observations are substantiated by Thomas (2013), Burpee and Fernandez (2014), and others who enumerated the suite of professional responsibilities commonly associated with SC librarians. Burpee and Fernandez's (2014) investigation emphasized the highly collaborative nature of SC librarianship, not only at the level of the practitioner's institution, but inter-institutionally and inter-professionally.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These observations are substantiated by Thomas (2013), Burpee and Fernandez (2014), and others who enumerated the suite of professional responsibilities commonly associated with SC librarians. Burpee and Fernandez's (2014) investigation emphasized the highly collaborative nature of SC librarianship, not only at the level of the practitioner's institution, but inter-institutionally and inter-professionally. They also underscored that all librarians, regardless of their title or main responsibilities, must familiarize themselves with SC issues in order to initiate and participate in successful communities of practice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation